Target mass corrections revisited - Steffens, F. M.; Melnitchouk, W. (American Physical Soc, 2006)
We propose a new implementation of target mass corrections to nucleon structure functions which, unlike existing treatments, has the correct kinematic threshold behavior at finite Q(2) in the x -> 1 limit. We illustrate the differences between the new approach and existing prescriptions by considering specific examples for the F-2 and F-L structure functions, and discuss the broader implications of our results, which call into question the notion of universal parton distribution at finite Q(2).